Analyzed The Resistant Starch Content of Some Types of Sago Starch In Embarrassment with Heating Temperature Variations - Lapu, Petrus; Telussa, Ivonne (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2013)
Analyzed the resistant starch content of some types of sago starch in embarrassment with heating temperature variations have been conducted. In this analysis was done processing sago starch suspension, determination of the fat content of flour, qualitative test and analysis of starch digestibility and resistant starch manufacture of some types of sago starch in Maluku (sago ihur, sashes, molat) by varying the temperature of the heating method. The results were obtained moisture content of the sample base for this type of sago ihur 49.61%, 45.85% and sashes molat 47.77% while for the corn starch to the type ihur 9.329%, 6,245% and Molat sashes 5,793% while the tannin-free corn starch to type ihur 5.362%, 5,407% and molat sashes 4,719% and ash content of corn starch to the type ihur 0.09656%, 0.0761% and molat sashes 0.07146%. Glucose levels in samples of corn starch (type ihur, sashes and Molat) is hydrolyzed by the enzyme pancreatin is greater than the resistant starch glucose levels ranged from 1-1.4 mg / mL whereas for resistant starch samples with smaller temperature variation which is equal to 0.6-1.0 mg / mL.